2023
DOI: 10.1007/s10113-023-02045-y
|View full text |Cite
|
Sign up to set email alerts
|

Can the Middle East-North Africa region mitigate the rise of its food import dependency under climate change?

Abstract: The dependence on imports of the Middle East and North Africa (MENA) region for its food needs has increased steadily since the early 1960s, from 10% to about 40%. This import dependence could continue to rise in coming decades due to the projected MENA population growth and the expected negative impacts of climate change on the region’s natural resources and agricultural performances. To what extent the food import dependency of the MENA region will continue to increase up to 2050 and how the region could mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Recent studies have already highlighted the adverse effects of grain import dependency in MENA ( 16 , 17 ) and shown that it is expected to increase in the years ahead ( 18 ), potentially hindering the region’s ability to address its food insecurity. They have also highlighted the region’s vulnerability to trade disruptions caused by the war in Ukraine and COVID-19 ( 19 , 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have already highlighted the adverse effects of grain import dependency in MENA ( 16 , 17 ) and shown that it is expected to increase in the years ahead ( 18 ), potentially hindering the region’s ability to address its food insecurity. They have also highlighted the region’s vulnerability to trade disruptions caused by the war in Ukraine and COVID-19 ( 19 , 20 ).…”
Section: Introductionmentioning
confidence: 99%